Thermal Effect Monitoring System of Dry-Type Smoothing Reactor - Jingen Hu; Minglei Shi; Chenhua Jiao; Guichi Zhu (Journal of Control Science and Engineering)
In order to study the influence of harmonic current loss characteristics on the thermal effect of UHV dry smoothing reactor, the author proposes a thermal effect monitoring system under the loss mechanism of dry smoothing reactor. By adding the electromagnetic loss density to the temperature field as a heat source, the electromagnetic-thermal multiphysics mapping relationship is established, the convective heat transfer process is more accurately simulated, and the temperature rise calculation is realized. Finally, the temperature rise test of the dry-type smoothing reactor is carried out. Experimental results show that using the calculation method considering the characteristics of harmonic loss, the maximum error between the calculated value and the experimental value is 9.1%, the average error is 4.34%, and the temperature rise distribution law is in good agreement. The system meets the requirements of engineering precision and provides the corresponding theoretical basis for engineering designers.